Two-Layer MPC Virtual Inertia Control Strategy for Small-Scale Variable-Speed Pumped Storage Unit with Full-Size Converter - Changhao XU; Weidong GUAN; Yue WANG; Jinshuai ZHANG; Peng WANG; Ning ZHOU; Bowen SHANG (Zhongguo dianli)
The development of miniature variable-speed pumped storage on the distribution side is conducive to enhancing the ability of the distribution network to accomodate renewable energies in a more environmentally friendly way. In this paper, a two-layer model predictive control (MPC) virtual inertia control strategy for variable-speed pumped storage unit with full-size converter is proposed. The strategy contains a standard-layer MPC and an auxiliary-layer MPC. The standard-layer MPC generates minimized frequency deviation signals based on a determined system prediction model and passes them to the auxiliary-layer MPC, which considers the stochastic nature of the PV generation with the goal of tracking the frequency deviation predicted by the standard-layer MPC and generates both the power and the guide vane control signals. The simulation of a test system containing a pumped storage unit with full-size converter shows that the proposed control strategy has good frequency-regulating performance, which is helpful to enhancing the PV accomodation capability of the distribution networks.